The effects of soygerm extracts on blood lipoproteins, antioxidative capacity and urinary estrogen metabolites in postmenopausal women on hormone therapy - Hsu, I.P; Jou, H.J; Huang, C.W; Wang, T.A; Wu, W.H (International journal of gynecology and obstetrics, 2007)
Abstract Objective To evaluate the effects of soygerm isoflavones extracts on blood lipoproteins, antioxidative capacity and urinary estrogen metabolites in postmenopausal women who receive hormone therapy (HT). Method Thirty-nine volunteers receiving HT were recruited, and 33 completed the study. All subjects received 6 g of soygerm extracts per day for 4 weeks. Blood and urine samples were collected for study at the beginning and at the end of study. Result Plasma HDL-C levels increased markedly with significant decreases of plasma LDL-C/HDL-C ratio and LDL–TG levels. The lag time of conjugated dienes formation prolonged for 9.9% and thiobarbituric acid reactive substances production in copper-catalyzed oxidation of LDL decreased. The differences were statistically significant. Urinary ratio of 2-OHE1 to 16α-OHE1 increased without statistical significance. Conclusion Soygerm extracts may improve serum lipid profile in postmenopausal Taiwanese women who receive HT, and probably provide a favorable effect on estrogen metabolism.